A Literary and Critical Analysis of British Orientalist D. S. Margoliouth’s Views Concerning Islamic Calendar - Shah, Aliya; Rahman, Atta ur (Journal of Islamic and Religious Studies, 2022)
This study is intended to critically analyze D.S. Margoliouth’s allegations regarding Hijri calendar. The orientalists generally try to control the superb and wonderful teachings of Prophet Muhammad S.A.W as well as the beauty of Islam. D.S Margoliouth is one of the narrow minded and prejudiced orientalists. Besides his other hazy and groundless allegations, he has also alleged the Hijri calendar. This article is, therefore, apprehensive to elucidate the allegations of D.S. Margoliouth about Hijri calendar and to conclude that the allegations are incompetent, valueless, and lethal about Islamic lunar calendar. Moreover, this article also argues that D.S. Margoliouth is partial and biased in his views about Hijri calendar.